STRATEGIC TASKS OF ENSURING YOUTH PARTICIPATION IN STATE POWER AND GOVERNANCE IN THE NEW UZBEKISTAN - Abrarov Islomiddin Jamolovich (The Conference Hub, 2026)
As a result of the socio-political reforms being implemented in our country, youth are emerging as a leading force in the development of society. In particular, ensuring the active participation of young people in the system of state power and governance is laying the groundwork for building a democratic state and establishing transparent and effective administration.In the practice of developed foreign countries, ensuring youth participation in state power and governance is considered one of the key indicators of building a democratic society. In Uzbekistan, recent reforms have similarly focused on actively involving young people in state and societal governance.